Identification and analysis of proline-rich proteins and hybrid proline-rich proteins super family genes from Sorghum bicolor and their expression patterns to abiotic stress and zinc stimuli - Rajasheker, Guddimalli; Nagaraju, Marka; Varghese, Rinku Polachirakkal; Jalaja, Naravula; Somanaboina, Anil Kumar; Singam, Prashant; Ramakrishna, Chintala; Penna, Suprasanna; Sreenivasulu, Nese; Kishor, P. B. Kavi (Frontiers Media, 2022)
Systematic genome-wide analysis of Sorghum bicolor revealed the identification of a total of 48 homologous genes comprising 21 proline-rich proteins (PRPs) and 27 hybrid proline-rich proteins (HyPRPs). Comprehensive scrutiny of these gene homologs was conducted for gene structure, phylogenetic investigations, chromosome mapping, and subcellular localization of proteins. Promoter analysis uncovered the regions rich with phosphorous- (BIHD), ammonium-, sulfur-responsive (SURE), and iron starvation-responsive (IRO2) along with biotic, abiotic, and development-specific cis-elements. Further, PRPs exhibit more methylation and acetylation sites in comparison with HyPRPs. miRNAs have been predicted which might play a role in cleavage and translation inhibition. Several of the SbPRP genes were stimulated in a tissue-specific manner under drought, salt, heat, and cold stresses. Additionally, exposure of plants to abscisic acid (ABA) and zinc (Zn) also triggered PRP genes in a tissue-dependent way. Among them, SbPRP17 has been found upregulated markedly in all tissues irrespective of the stress imposed. The expressions of SbHyPRPs, especially SbHyPRP2, SbHyPRP6, and SbHyPRP17 were activated under all stresses in all three tissues. On the other hand, SbHyPRP8 (root only) and SbHyPRP12 (all three tissues) were highly responsive to cold stress and ABA while SbHyPRP26 was induced by drought and Zn in the stem. Taken together, this study indicates the critical roles that SbPRPs and SbHyPRPs play during diverse abiotic stress conditions and notably the plausible roles that these genes play upon exposure to zinc, the crucial micronutrient in plants.